2019
DOI: 10.1016/j.cmet.2019.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Medicine in the Fourth Dimension

Abstract: The importance of circadian biology has rarely been considered in pre-clinical studies, and even more when translating to the bedside. Circadian biology is becoming a critical factor for improving drug efficacy and diminishing drug toxicity. Indeed, there is emerging evidence showing that some drugs are more effective at nighttime than daytime, whereas for others it is the opposite. This suggests that the biology of the target cell will determine how an organ will respond to a drug at a specific time of the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
215
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(234 citation statements)
references
References 157 publications
4
215
0
1
Order By: Relevance
“…Interestingly Besides, our genetic alteration analysis also suggested the low mutation rates of these CCRGs in the risk-score model, which was also in line with the current view that CCRGs were evolutionarily conserved in eukaryotes (18).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly Besides, our genetic alteration analysis also suggested the low mutation rates of these CCRGs in the risk-score model, which was also in line with the current view that CCRGs were evolutionarily conserved in eukaryotes (18).…”
Section: Discussionsupporting
confidence: 89%
“…Besides, our genetic alteration analysis also suggested the low mutation rates of these CCRGs in the riskscore model, which was also in line with the current view that CCRGs were evolutionarily conserved in eukaryotes (18). Moreover, this conservatism would affect plenty of critical cell functions, such as immunomodulatory.…”
Section: Discussionsupporting
confidence: 88%
“…Circadian biology is being considered as the fourth dimension of modern medicine (18). There is clear evidence for the differential expression of CCRGs in a variety of diseases, and cancers are no exception (19).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that circadian rhythm disruptions lead to an increased likelihood of mammary tumor development is supported by studies that female workers taking frequent night shifts have disrupted internal clocks and an increased risk of developing breast cancer (BC) (Davis et al, 2001;Schernhammer et al, 2001;Wegrzyn et al, 2017). It has been reported that circadian genes have anti-tumor roles in multiple cancer types (de Assis et al, Papagiannakopoulos et al, 2016;Tang et al, 2017) and may act as tumor suppressors by regulating a wide variety of pathophysiological events, including cellular metabolism and pathogenesis of cancer (Cederroth et al, 2019;Lesicka et al, 2018;Lin and Farkas, 2018). Indeed, disrupted circadian rhythm likely affects multiple hallmarks of cancer, including proliferative signaling maintenance, cell death resistance, replicative immortality, invasion and metastasis activation, and energy metabolism reconfiguration (Hanahan and Weinberg, 2011).…”
Section: Introductionmentioning
confidence: 99%